Creating a Collaboration Framework to Evaluate International University‐led Water Research Partnerships. (14th January 2021) - Mazer, Katy E.; Erwin, Anna; Popovici, Ruxandra; Bocardo‐Delgado, Edwin; Bowling, Laura C.; Ma, Zhao; Prokopy, Linda S.; Zeballos‐Velarde, Carlos
Abstract: In a globalized world, universities are forming partnerships to solve today's water‐related challenges, such as increasing water scarcity and diminished water quality. Over the past 20 years, international university‐led water research partnerships have been growing in number, including between the U.S. and countries in the Global South. While there are several examples of guidelines and best practices for executing collaborations, none focus on this type of partnership. Additionally, many international collaborations are formed between universities that have little previous experience in developing these types of partnerships. Often, critiques of partnerships happen after initiation and point to structural barriers and best practices for future collaborations, but few offer practical guidance on overcoming obstacles early on, amid an imperfect partnership. In this paper, we created a flexible collaboration framework which can be used as an evaluative tool. To model this, we conducted an internal evaluation of the Sustainable Water Management team of the Arequipa Nexus Institute, a collaboration designed to build research capacity at the Universidad Nacional de San Agustín to address local issues related to agriculture, natural resource management, and environmental change. Results highlighted project strengths and weaknesses and offered strategies to address challenges that many collaborations face. This strategy identification can serve as a guideline for improving the implementation of new or existing international university‐led water research partnerships and help partners as they confront challenges at every stage of the partnership. The evaluation shows the effectiveness of using a collaboration framework as an assessment tool for international university‐led water research partnerships.